Pengaruh Model Moral Reasoning pada Mata Pelajaran Pendidikan Pancasila Terhadap Pengambilan Keputusan Moral di Kelas XI MA Al-Hadi Girikusuma Kecamatan Mranggen Kabupaten Demak: The Influence of the Moral Reasoning Model in Pancasila Education Subjects on Moral Decision Making in Class XI of MA Al-Hadi Girikusuma, Mranggen District, Demak Regency - Maulid Diana, Messy; Widayati, Sri; Baehaqi, M. Lutfi (Lembaga Bale Literasi, 2025)
This study is motivated by the lack of moral decision-making in the learning process. The purpose of this research is to analyze the effect of the Moral Reasoning Model in the Pancasila Education subject on moral decision-making among Grade XI students of MA Al-Hadi Girikusuma, Mranggen District, Demak Regency. This research employs a quantitative approach. The subjects of this study were students of classes XI.1 and XI.3, with a total population of 64 students. The sampling technique used was cluster random sampling. Data were collected through questionnaires, while data analysis was conducted using normality tests, homogeneity tests, biserial correlation tests, and t-tests with the assistance of SPSS 23. The results indicate that the Moral Reasoning Model in Pancasila Education has a significant influence on moral decision-making, as shown by the normality test (0.200 > 0.05) and the homogeneity test (0.355 > 0.05). Furthermore, the Moral Reasoning Model also shows a correlation with moral decision-making, indicated by the biserial correlation test value of 0.1998 and the t-test result of 1.720 > 1.166 (t-table).